2007
DOI: 10.1080/03079450701589175
|View full text |Cite
|
Sign up to set email alerts
|

A field study on the significance of vaccination against infectious bursal disease virus (IBDV) at the optimal time point in broiler flocks with maternally derived IBDV antibodies

Abstract: The right strategy for infectious bursal disease (IBD) control and its success rate under field conditions depends on hygiene management, IBD field pressure, level and variation in maternally derived IBD antibodies, and the IBD vaccine strains to be used. Usually, standard vaccination programmes are used, which are not always adapted to the specific conditions on the farm and to the immune status of chickens. Employing the ''Deventer formula'' may help to estimate the optimal time for vaccination for a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…As such, the benefits of maternal antibodies could be of greater importance, while the potential developmental costs are diminished, for these species. The idea that maternally derived antibodies have a blocking effect on offspring immunity has been important for the development of vaccination schedules in human and veterinary medicine (Block et al 2007;Siegrist 2007). Although the effect of maternal antibodies on immune responses is well documented, it is not clear whether this blocking effect is exclusive to T-cellmediated responses or whether it might also affect lymphocyte development (Carlier & Truyens 1995).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the benefits of maternal antibodies could be of greater importance, while the potential developmental costs are diminished, for these species. The idea that maternally derived antibodies have a blocking effect on offspring immunity has been important for the development of vaccination schedules in human and veterinary medicine (Block et al 2007;Siegrist 2007). Although the effect of maternal antibodies on immune responses is well documented, it is not clear whether this blocking effect is exclusive to T-cellmediated responses or whether it might also affect lymphocyte development (Carlier & Truyens 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination strategy is dual: passive protection induced by the maternally-derived antibodies (MDA) and active immunization of the progeny by its vaccination [2,3], taking into account the interference between these MDAs and the live vaccine take. A very virulent form of the disease was described around twenty years ago [4,5] and is still considered as a major treat to the poultry industry everywhere in the world [6], and more recently in the United States of America [7].…”
Section: Introductionmentioning
confidence: 99%
“…Block et al (2007) demonstrated that vaccination against IBD 24 hours before or 3 days after the estimated optimal time for vaccination resulted in a satisfactory serological response (14 days post vaccination) in evaluated chicken flocks. In the field "500" vaccines are most often given to birds on the 16 th day of life, as a routine, in cases where Deventer formula is not implemented.…”
Section: Resultsmentioning
confidence: 91%
“…The layout of estimated optimal days for vaccination of broiler chickens against IBD in regard to the sampling age is summarized in table 2. In the light of the results of Block et al (2007), our findings indicate that the 16 th day vaccination routine would result in satisfactory vaccine-induced immunity in 79.01 and 54.71% of the analyzed cases where birds were still protected by the MDA (in regard to vaccinal MDA break-through; 16-17 th day of life) and in 98.76 and 100% of the cases in general (13-17 th day of life) if blood samples were collected 0-3 or 4-7 days after hatch respectively. The above data indicate that the accommodation period and other factors interfering with yolk sac resorption influence the outcome of chicken anti -IBD serum MDA level, which may affect vaccination schedule and efficiency.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation